2018
DOI: 10.5114/fn.2018.80863
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between plasma homocysteine and MTHFR gene polymorphism and white matter lesions

Abstract: This study aims to investigate the correlation between the plasma homocysteine (Hcy) level and methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism, and white matter lesions (WML). The plasma Hcy level and MTHFR C677T gene polymorphism in 104 patients with white matter lesions and 74 controls were measured. The severity of cerebral white matter was scored on the magnetic resonance imaging (MRI) images by the modified Scheltens scale (score of 0-30). The plasma Hcy level in the WML group was remarkabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Previous studies have shown that advanced age and elevated blood pressure are significant causes of arteriosclerosis WMLs (11). Furthermore, elevated homocysteine, a well-known risk factor for arteriosclerosis (11), was found to be higher in the patients with moderate-severe WMLs, which is consistent with previous findings that homocysteine levels are positively correlated with the volume of arteriosclerotic WMLs (33)(34)(35). Hence, the WMLs investigated in the current study was further indicated to be of the arteriosclerotic subtype.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown that advanced age and elevated blood pressure are significant causes of arteriosclerosis WMLs (11). Furthermore, elevated homocysteine, a well-known risk factor for arteriosclerosis (11), was found to be higher in the patients with moderate-severe WMLs, which is consistent with previous findings that homocysteine levels are positively correlated with the volume of arteriosclerotic WMLs (33)(34)(35). Hence, the WMLs investigated in the current study was further indicated to be of the arteriosclerotic subtype.…”
Section: Discussionsupporting
confidence: 90%
“…In the meta-analysis results published in 2019 and conducted in China in the elderly population with ischemic stroke, it was stated that the T allele of the C677T gene increased the ischemic stroke [41]. In the publication published in 2018 and investigating the relationship between white matter lesions and the genotypes of the MTHFR C677T gene, it was stated that the severity of white matter lesions was not related to the MTHFR C677T gene polymorphism [42].…”
Section: Discussionmentioning
confidence: 99%
“…There are studies on different prothrombotic gene mutations that are thought to be effective in the etiopathogenesis of cerebrovascular diseases. These studies focus on the methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C mutation [11][12][13][14]. The human MTHFR gene is localized on chromosome 1p36.3 and encodes the MTHFR enzyme consisting of 656 amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been demonstrated that the decrement in the activity of the MTHFR enzyme reduces the serum folate concentration and increases the homocysteine (Hcy) levels (Jacques et al 1996;Kerkeni et al 2006). In this regard, Li et al (2018) in a Chinese population found higher serum concentrations of Hcy in people with the TT genotype (MTHFR C677T polymorphism) compared to levels detected in individuals with CC or CT genotype (Li et al 2018).…”
Section: Introductionmentioning
confidence: 99%